RECENT ADVANCES IN DENTAL EDUCATION - Rajkumar Shancy Merlin, Arokia; Jayalakshmi,; Roy, Anitha (International Journal of Psychosocial Rehabilitation, 2020)
Dentistry is a branch of medicine that deals with the study, diagnosis, prevention and treatment of various disorders of the oral and maxillofacial region. Aspiring dentists educate themselves in a four-year course in a dental school wherein after completion, the individual receives a degree in dentistry, dental surgery or dental medicine depending upon the program offered. Education is a process of knowledge and awareness and must include both theoretical and practical knowledge to have a holistic education. With the varied changes in technology, biology and increasing research in medicine, there has also been considerable reformations in dental education as opposed to earlier times. This enhances the skills of the dental students in order to render proper service to the patients. However, the present reformations are unable to provide a long-lasting education and many of the reformations are still in the infant stage. A reformation is hence required to provide a long term learning experience and to inculcate an inquiring, proficient mind in the dental student. For instilling such characteristics in a student, timely changes in the curriculum is a necessity. The usage of technology such as VR and the addition of other advancements such as stimulation or case-based learning, prepares them to face a variety of cases and helps them in providing proper care to the patients. This article explores the various advancements that can be added into the curriculum and the advantages as well as disadvantages of the same. Medicine is a course where the individual is always a student, hence a long-term knowledge is a necessity to provide holistic care for the patient.